COMPARISON OF INTERMOLAR ARCH WIDTH BEFORE AND AFTER ALIGNMENT PHASE OF ORTHODONTIC TREATMENT IN CLASS II DIV 1 PATIENTS - Bushra Amin; Sadia Naureen; Hameed Ullah Jan; Tariq Hameed; Umer Hameed (Pakistan Oral & Dental Journal, 2021)
Arch width changes introduced from fixed appliance treatment are significant to the orthodontist. An understanding of these changes is of utmost vitality to the clinician in terms of treatment planning. The purpose of this study was to determine and compare the inter-molar arch width in classII div 1 cases before and four months into fixed orthodontic treatment It was a cross sectional interventive study carried out in orthodontic department of Armed Forces Institute of Dentistry AFID, Rawalpindi. 208 patients of class II div 1 malocclusion were selected by non probability purposive sampling. The age range of sample was 15-25 years. Upper arch impressions were taken and maxillary intermolar width was measured on the study casts before and six months into orthodontic treatment. Standard arch wires were used starting from .012 Nitinol upto .019x.028 Nitinol. Intermolar arch width was taken as the transverse distance from the central fossa of first molar on one side to the central fossa of first molar on the other side of the same arch. The pretreatment mean values of intermolar arch width in females and males were found to be 45.01 ± 2.4mm and 46.6 ± 2.6mm respectively. However, the posttreatment T2 mean intermolar arch width was found to be 46.7 ± 2.4mm in females and 48.4 ± 2.7mm in males.There was a mean increase of 1.7mm in pre and post treatment intermolar arch width so an orthodontist should be cautious in arch expansion mechanics specially when the treatment plan is non extraction.
Keywords: Intermolar Arch width; Arch form; Class II div 1 malocclusion